New findings on the action of hypericin in hypoxic cancer cells with a focus on the modulation of side population cells - Buľková, Viktória; Vargová, Jana; Babinčák, Marián; Jendželovský, Rastislav; Zdráhal, Zbyněk; Roudnický, Pavel; Košuth, Ján; Fedoročko, Peter (Biomedicine & pharmacotherapy, 2023)
The presence of key hypoxia regulators, namely, hypoxia-inducible factor (HIF)-1α or HIF-2α, in tumors is associated with poor patient prognosis. Hypoxia massively activates several genes, including the one encoding the BCRP transporter that proffers multidrug resistance to cancer cells through the xenobiotic efflux and is a determinant of the side population (SP) associated with cancer stem-like phenotypes. As natural medicine comes to the fore, it is instinctive to look for natural agents possessing powerful features against cancer resistance. Hypericin, a pleiotropic agent found in Hypericum plants, is a good example as it is a BCRP substrate and potential inhibitor, and an SP and HIF modulator. Here, we showed that hypericin efficiently accumulated in hypoxic cancer cells, degraded HIF-1/2α, and decreased BCRP efflux together with hypoxia, thus diminishing the SP population. On the contrary, this seemingly favorable result was accompanied by the stimulated migration of this minor population that preserved the SP phenotype. Because hypoxia unexpectedly decreased the BCRP level and SP fraction, we compared the SP and non-SP proteomes and their changes under hypoxia in the A549 cell line. We identified differences among protein groups connected to the epithelial-mesenchymal transition, although major changes were related to hypoxia, as the upregulation of many proteins, including serpin E1, PLOD2 and LOXL2, that ultimately contribute to the initiation of the metastatic cascade was detected. Altogether, this study helps in clarifying the innate and hypoxia-triggered resistance of cancer cells and highlights the ambivalent role of natural agents in the biology of these cells.
Keywords: nádorové proteiny; transkripční faktory bHLH; Gene Expression Regulation, Neoplastic; ECM reorganization; hypoxie buňky; Neoplasms; Cell Line, Tumor; Basic Helix-Loop-Helix Transcription Factors; regulace genové exprese u nádorů; Side-Population Cells; Hypoxia; ATP Binding Cassette Transporter, Subfamily G, Member 2; Side population; faktor 1 indukovatelný hypoxií - podjednotka alfa; vedlejší populace buněk; lidé; Cell Hypoxia; Hypericin; ABC transportér z rodiny G, člen 2; Humans; Neoplasm Proteins; Breast cancer resistance protein; nádory; Proteomics; nádorové buněčné linie; Hypoxia-Inducible Factor 1, alpha Subunit; hypoxie